Development of pedagogical conditions of a future educator’s training to art and speech activities of preschoolers - Batio, Maria (ScienceRise: Pedagogical Education, 2017)
Pedagogical conditions of realization of the technology of training of a future educator to the organization of art-speech activity of preschool children were determined in this research, according to the culturological, activity, hermeneutic and creative scientific approaches: а) creation of the emotional-creative context of students’ training to the organization of art-speech children’s activity. b) students’ dipping into the active-creative art-speech activity; c) support of integration of types of art-speech activity in the professional training of a future educator; d) introduction of pedagogical practices of tasks on the development of art-speech activity of preschoolers into curriculums; e) use of text-centrism in the training of a future educator to the art-speech activity of preschoolers. The following methods of the technology realization were characterized: а) empathy (self-association); b) solution of розв’язання педагогічних ситуацій; c) staging and dramatization; d) business game; e) projects; f) ETT methods (method of tests and mistakes, methods of morphological analysis, synectics method, method of control tasks, method of focal objects); g) activity research; h) pedagogical diary i) intervision; j) work with texts. It was accented on the fact that the technology realization becomes possible due to the introduction of such forms of the work with students as an interactive lecture and training. Future educators study at them: а) to formulate pedagogical maxims; b) to compose papers by different bases; c) to create child fairy tales, sink vanes, verses; d) to realize observations and recording of child dialogues; e) to perform interactive plays for children, to organize literature projects; f) to solve pedagogical situations and methodological tasks; g) to develop and to carry out integrated activities on the base of art synthesis. There was substantiated the necessity of observing separated pedagogical conditions at each stage of the developed technology (conceptual, content, procedural)